Theories of Learning and the Real World: An Integrated Teaching Technique Using Empirical Research and Film - Karen Michele Zabrucky; Nannette Evans Commander (Networks: An Online Journal for Teacher Research, 2012)
As instructors of an educational psychology course focusing on theories of learning, we are aware of the trepidation our students may experience on the first day of class and beyond. Theories of learning sound a bit daunting and, unfortunately, disconnected from the real world. Of course, our students' conceptualizations of learning theories are quite different from our own; that they are interesting, informative, and relevant to understanding how individuals learn in a variety of contexts as well as how best to instruct others (Schneider, 2008).